(untitled) (The Pakistan Development Review, 1998)
This paper gives an overview of socio-cultural, religious and political background of Pakistani society and examines the current status of women utilising data from Pakistan Fertility and Family planning Survey 1996-97. The low status of women is one of the many factors in Pakistani society, which interfere with the achievement of development goals. The success of family planning intervention also mainly depends upon the cooperation and involvement of women. The traditional social structures and norms that limit women’s roles may limit their ability to contribute in efforts to control population growth. Some indicators, such as education of women, employment of women, women’s participation in domestic and child related decisions, women’s mobility, communication about family planning, religion and family planning, have been examined from Pakistan Fertility and Family Planning Survey (1996-97) [For detail of PFFPS, see Hakim et at. (1998)]. Data reveal that there is a little improvement in the social indicators of status of women in Pakistan, however, it is still very low which inhibit their participation in education and in the labour force as well as encouraging their high fertility. Maintenance of traditional Islamic and cultural restrictions on women may also conflict with the achievement of development goals in family planning. Hence an examination is required of Islamic teachings and customary laws affecting the status of women in Pakistani society and the family which ultimately restrict women from adopting family planning measures.